Long-term outcome of childhood and adolescent patients with craniopharyngiomas: a single center retrospective experience - Li-Yuan Zhang; Han-Ze Du; Ting-Ting Lu; Shuai-Hua Song; Rong Xu; Yue Jiang; Hui Pan (BMC Cancer)
Abstract Background The treatment of craniopharyngiomas (CPs) poses challenges due to their proximity to critical neural structures, the risk of serious complications, and the impairment of quality of life after treatment. However, long-term prognostic data are still scarce. Therefore, the purpose of this retrospective study is to evaluate the long-term outcomes of patients with CPs after treatment. Material and method Our center retrospectively collected data on 83 children and adolescents who underwent craniopharyngioma surgery between 2001 and 2020. The medical records and radiological examination results of the patient were reviewed. Results Outcomes were analysed for 80/83 patients who completed follow-up: 50 males (62.5%) and 30 females (37.5%), the median age at the time of diagnosis 8.4 (5.3–12.2) years. The median follow-up time was 136 (61–280) months. The 5-, 10- and 15-year overall survival (OS) rates were 100%, 98.3%, and 94.6%, respectively. Accordingly, the disease-specific survival (DSS) rates were 100%, 98.3% and 94.6%, respectively. Overall progression-free survival (PFS) rates after 5, 10 and 15 years of follow-up in the entire group were 85.4%, 72.2% and 70.1%, respectively. Multivariate analysis found that surgical resection grade was only associated with PFS outcomes [ HR = 0.031 (95% CI: 0.006, 0.163), P < 0.001], without improving OS or DSS. After undergoing recombinant human growth hormone (rhGH) replacement therapy, the total cholesterol (TC) level decreased by 0.90 mmol/L compared to baseline (P = 0.002), and the low-density lipoprotein cholesterol (LDL-C) level decreased by 0.73 mmol/L compared to baseline (P = 0.010). For liver function, compared with baseline data, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) showed a downward trend, but did not reach a statistically significant level (P > 0.05). Conclusion Surgical treatment of CPs provides good long-time OS and DSS, even though combined with radiotherapy in only selected cases. Gross total resection (GTR) is individual positive prognostic factor. rhGH replacement could improve CPs lipid profile.